A Decision Support Method for the Selection of Object Management Systems - Dewal, Sanjay; Emmerich, Wolfgang; Lichtinghagen, Karsten (Universität Dortmund, 2002)
With the increasing demand for highly complex, integrated and application domain specific systems engineering environments (SEEs) more or less specialized components of the SEEs are developed. An important component is the database management system (DBMS). It is generally accepted that conventional DBMSs are not useful to fulfill the requirements on highly complex, persistent data structures. Rather specialized DBMSs, namely object management systems (OMS), have been developed for fulfilling the enhanced requirements. An advantage of OMSs is that they further enhance the integration not only of data but also of processes. Currently several specialized OMSs with significantly different properties such as the data model, architecture and performance are available. Thus it is very difficult for an SEE developer to select the most appropriate OMS for his SEE. In this paper we have proposed a decision support method which enables an SEE developer to identify his requirements and to compare the evaluation results of different OMSs. Additionally we present a practical experiment where we have applied the decision support method for comparing different OMSs. Experiences of the investigation are presented briefly.
Internes Memorandum des Lehrstuhls für Software-Technologie / Fachbereich Informatik, Universität Dortmund ; 61
Keywords: 004